2019
DOI: 10.1007/s42995-019-00015-0
|View full text |Cite
|
Sign up to set email alerts
|

Our recent progress in epigenetic research using the model ciliate, Tetrahymena thermophila

Abstract: Epigenetic research focuses on heritable changes beyond the DNA sequence, which has led to a revolution in biological studies and benefits in many other fields. The well-known model ciliate, Tetrahymena thermophila offers a unique system for epigenetic studies due to its nuclear dimorphism and special mode of sexual reproduction (conjugation), as well as abundant genomic resources and genetic tools. In this paper, we summarize recent progress made by our research team and collaborators in understanding epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 99 publications
3
27
0
Order By: Relevance
“…Previous morphogenetic studies of ciliates [14,15,[70][71][72] have shown that many biological processes, including somatic cortex morphogenesis, stomatogenesis, and organelle morphogenesis, occur at stage D. Transcriptomes from the G and D stages ( Figure 4C) and RT-qPCR analyses revealed that phosphotransferase activity might be related to cortex modifications [73] as it was enriched during the D stage. Common amino acid residues typically phosphorylated by kinases include serine, threonine, and tyrosine.…”
Section: Comparisons With Previous Studies Focusing On the Cell Cyclementioning
confidence: 87%
See 3 more Smart Citations
“…Previous morphogenetic studies of ciliates [14,15,[70][71][72] have shown that many biological processes, including somatic cortex morphogenesis, stomatogenesis, and organelle morphogenesis, occur at stage D. Transcriptomes from the G and D stages ( Figure 4C) and RT-qPCR analyses revealed that phosphotransferase activity might be related to cortex modifications [73] as it was enriched during the D stage. Common amino acid residues typically phosphorylated by kinases include serine, threonine, and tyrosine.…”
Section: Comparisons With Previous Studies Focusing On the Cell Cyclementioning
confidence: 87%
“…Ciliates, a group of unicellular eukaryotes, have been used extensively as model organisms to study a broad range of topics due to dual genome architecture, unique macronuclear genome characters ( Figure 1), and complex morphology [14][15][16][17][18][19][20][21][22][23][24]. Recently, molecular events underlying the sexual cell cycle of the model ciliate Tetrahymena thermophila were examined.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The model microbial eukaryote Tetrahymena has facilitated numerous studies and benefited many fields. In our first paper, Cheng et al (2019) summarize their progress in understanding epigenetic mechanisms using Tetrahymena. This review reports their efforts to generate a high-resolution DNA N 6 -methyladenine (6 mA) map, evaluate the determinants for nucleosome distribution, demonstrate the roles of RNAi-dependent Polycomb repression pathways on transposable elements, and discover the functions of histone methylation in replication elongation.…”
mentioning
confidence: 99%